Carbon Fibers: Origin and Control of Polyacrylonitrile Alignments on Carbon Nanotubes and Graphene Nanoribbons (Adv. Funct. Mater. 15/2018). (14th April 2018) - Lee, Juho; Choi, Ji Il; Cho, Art E.; Kumar, Satish; Jang, Seung Soon; Kim, Yong‐Hoon
Abstract : In article1706970, Seung Soon Jang, Yong‐Hoon Kim, and co‐workers investigate the interface between polyacrylonitrile (PAN), and graphene nanoribbons (GNR) or carbon nanotubes (CNT). The cover describes 1) the preferred linear alignment of PAN on GNR/CNT and the dominance of lying‐down PAN configurations, 2) the strong yet balanced charge accumulation and depletion on GNR induced by PAN adsorption, and 3) the superiority of GNRs over CNTs as a carbon nano‐reinforcement elements.